PERAN E-COMMERCE DALAM PERSPEKTIF EKONOMI SYARIAH - Dwi Priyadi; Agus Marimin; Wikan Budi Utami (ITB AAS INDONESIA Surakarta, 2026)
The rapid development of e-commerce has transformed commercial activities into a more efficient and accessible digital trading system. However, digital transactions also present challenges related to compliance with Islamic economic principles, including the potential presence of riba, gharar, and a lack of transparency in transactions. This study aims to analyze the role of e-commerce from the perspective of Islamic economics, examine the implementation of Sharia principles on e-commerce platforms in Indonesia, and identify the challenges to their development. The study employed a descriptive qualitative approach using library research and document analysis. Data were collected from secondary sources, including books, scientific articles, regulations, fatwas, and official institutional reports, and analyzed using thematic content analysis. The findings indicate that e-commerce plays an important role in expanding market access, empowering micro, small, and medium enterprises (MSMEs), enhancing Islamic financial literacy, and supporting the development of the halal economic ecosystem. The implementation of Sharia principles is reflected in the provision of halal products, the application of valid Islamic contracts, transparent transaction mechanisms, and interest-free financial services. Nevertheless, the development of Sharia e-commerce continues to face challenges, including limited Sharia digital literacy, the absence of comprehensive operational standards, and the need to strengthen Sharia compliance supervision. Therefore, collaboration among the government, regulators, business actors, and Islamic financial institutions is essential to establish a transparent, inclusive, and sustainable Sharia e-commerce ecosystem.